Case report: Concurrent intravestibular schwannoma mimicking Ménière's disease and cochlear hydrops detected via delayed three-dimensional fluid-attenuated inversion recovery magnetic resonance imaging - Nishimura, Koji; Murofushi, Toshihisa; Hakuba, Nobuhiro (Frontiers in Neurology, 2022)
Objective To present a case of intralabyrinthine schwannoma (ILS) presenting as Ménière's disease diagnosed via 4-h delayed gadolinium-enhanced three-dimensional fluid-attenuated inversion recovery magnetic resonance imaging (3D-FLAIR MRI) and treated successfully using the translabyrinthine approach. Patient A patient who was diagnosed with intravestibular ILS. Interventions The patient underwent comprehensive preoperative neurological examinations and MRI. The tumor was resected using the translabyrinthine approach and was pathologically confirmed as schwannoma based on the surgical specimen. Main outcome measures Preoperative audiogram and vestibular test findings and MRI images. Results Preoperatively, pure-tone audiogram showed progressive sensorineural hearing loss only on the affected side. The video head impulse test and vestibular evoked myogenic potential test showed vestibular dysfunction on the affected ear. Immediate gadolinium-enhanced T1-weighted MRI revealed an enhanced region in the vestibule. Meanwhile, magnetic resonance cisternography showed a filling defect. Delayed 3D-FLAIR MRI revealed a signal void in the scala media of the cochlea indicative of cochlear hydrops, and a strong signal in the perilymph at the basal cochlea suggestive of impaired blood–labyrinthine barrier. Conclusion Delayed 3D-FLAIR MRI is useful in diagnosing concurrent ILSs and endolymphatic hydrops.